A143 THE CANADIAN LANDSCAPE OF IBD CARE: ARE WE KEEPING PACE? PRELIMINARY RESULTS FROM A NATIONWIDE SURVEY. (1st March 2018) - Miles, M; Pena-Sanchez, J; Heisler, C; Jones, J
Abstract: Background: Patients with inflammatory bowel disease (IBD) require lifelong medical and surgical management of their disease. Globally, many institutions have adopted integrated collaborative care models to improve patient care. Studies of these dedicated IBD services have shown they improve patient outcomes and quality of life. Little is known, however, what models of care for the management of patients with IBD are currently used across Canada. Aims: The objectives of this study are to 1) determine the structure and processes used in clinics providing care for patients with IBD across Canada, 2) understand how IBD patients access IBD clinics across Canada, 3) identify the IBD practitioners and allied health professionals working with IBD clinics across Canada, and 4) determine the process and structure of referral pathways and clinical visits for IBD patients. Methods: Evidence-based survey development methods were used to develop a peer-reviewed and piloted, web-based questionnaire to survey Canadian gastroenterologists who provide care for IBD patients. The questionnaire was developed using Novi Survey software. The contact information for each gastroenterologist in Canada was acquired using a database provided by Scott's Directories. Participants' lists were finalized after cross-referencing the Scott's database with gastroenterologists listed by the Royal College of Physicians and Surgeons. In October 2017, the entire target population was invited to participate in the survey using the Dillman's Tailored Design methodology. Results: This work is in progress. To date, 14/583 (3%) survey questionnaires have been received from 7 provinces. Nine (65%) respondents are male and the mean age is 45 (SD=10) years. Working in or affiliated with most respondent IBD clinics are gastroenterologists specializing in IBD (71%), medical residents (71%), medical students (64%), gastroenterology residents (64%), IBD nurse non-practitioners (64%), research nurses (64%) general gastroenterologists (57%), IBD nurse practitioners (57%), dieticians (57%) and radiologists (57%). Few respondent IBD clinics have nurse educators (36%), general surgeons (36%), colorectal surgeons (36%), ophthalmologists (36%), social workers (36%), nurse navigators (29%) or psychiatrists (21%) working in or affiliated with them. Conclusions: IBD in Canada represents a significant burden of illness. Most of the respondents to date work in IBD clinics comprised of gastroenterologists, trainees, IBD nurses, research nurses and dieticians while few work with nurse educators or navigators, surgeons, social workers or psychiatrists. Given the limited number of responses to date the sample thus far is likely not representative and the final results of this survey will be presented once the survey distribution process is complete. Funding Agencies: None